Emerson, romanticism, and intuitive reason the transatlantic "light of all our day" - Keane, Patrick J. (Univ. of Missouri Press, 2005)
"Comparative study in transatlantic Romanticism that traces the links between German idealism, British Romanticism (Wordsworth, Coleridge, Carlyle), and American Transcendentalism. Focuses on Emerson's development and use of the concept of intuitive Reason, which became the intellectual and emotional foundation of American Transcendentalism"--Provided by publisher.